Comparative assessment of efficacy and safety of ambrisentan and bosentan in patients with pulmonary arterial hypertension: A meta‐analysis. (28th July 2021) - Zhao, Qinhua; Guo, Na; Chen, Jun; Parks, Daniel; Tian, Zhuang
Abstract: What is known and objective: Two endothelin receptor antagonists, ambrisentan and bosentan, have been demonstrated to be effective individually compared with placebo in the treatment of patients with pulmonary arterial hypertension (PAH). This network meta‐analysis compared the efficacy and safety of ambrisentan and bosentan in patients with PAH. Methods: Clinical trials were identified from the Cochrane Central Register of Controlled Trials (CENTRAL/CCTR), EMBASE and PubMed databases. Weighted mean differences (MD) with 95% confidence intervals (CI) were calculated for continuous outcomes (6‐min walk distance [6MWD] and Borg dyspnoea index [BDI]). Hazard ratio (HR) was calculated for binary outcomes, including clinical worsening, discontinuation due to adverse events (AEs) and liver dysfunction. Surface under cumulative ranking curve (SUCRA) was used to rank the treatments in each index. Results: Five clinical trials from four published studies (total patients: n = 920) were included. Ambrisentan and bosentan showed no significant difference in 6MWD (MD: −1.32; 95% CI: −27.87, 25.31, SUCRA score: ambrisentan 0.73, bosentan 0.77), BDI (MD: −0.16; 95% CI: −0.98, 0.65, SUCRA score: ambrisentan 0.83, bosentan 0.66), clinical worsening (HR: 0.99; 95% CI: 0.33, 2.94, SUCRA score: ambrisentan 0.75, bosentan 0.74) and discontinuation due to AEs (HR: 0.84; 95% CI: 0.11, 5.86, SUCRA score: ambrisentan 0.47, bosentan 0.57). However, ambrisentan was significantly better than bosentan with respect to abnormal liver function (HR: 23.18; 95% CI: 2.24, 377.20, SUCRA score: ambrisentan 0.99, bosentan 0.02). What is new and conclusion: The results of this network meta‐analysis suggest that ambrisentan was similar to bosentan in efficacy, while it exhibited better tolerability with respect to abnormal liver function in comparison with bosentan, in patients with PAH. Abstract : Ambrisentan and bosentan have been demonstrated to be effective individually compared with placebo in the treatment of patients with pulmonary arterial hypertension. This network meta‐analysis compared their efficacy and safety and showed that ambrisentan was similar to bosentan in efficacy, while it exhibited better tolerability with respect to liver function abnormalities in comparison with bosentan.